Ten years of Linguistics in the Pub. Issue 3 (3rd July 2021) - Gawne, Lauren; Singer, Ruth
ABSTRACT: In December 2009 the first 'Linguistics in the Pub' event was held in Melbourne. For over a decade Linguistics in the Pub (LIP) has been a space for linguists, language workers and language activists to discuss a wide range of topics, covering practical, theoretical and ethical elements of language work. In this paper we provide an overview of the themes that have emerged from these discussions. LIP events have been in step with major shifts in language documentation over the last decade including the decolonization of research, critical approaches to linguistic data management and engaging in public discourse around minoritized languages. Most importantly, LIP provides a space for peer learning, professional development and engagement with topics beyond core-curriculum for junior researchers, in which LIP creates a transparent and equitable approach to scholarly support. We conclude the article by providing instructions and insights for setting up LIP-style events, for other researchers who are interested in replicating this model of capacity building in language documentation, linguistics more broadly or other disciplines.